Investigation of the Image Contrast in an Ultra-Low Voltage Scanning Electron Microscope Using an Auger Electron Spectrometer. (August 2020) - Sakuda, Yusuke; Asahina, Shunsuke; Togashi, Takanari; Terasaki, Osamu; Kurihara, Masato
Abstract: Abstract : Surface-sensitive information on a bulk sample can be obtained by using a low incident electron energy (low accelerating voltage/landing voltage) in a scanning electron microscope (SEM). However, topography and composition contrast obtained at low incident electron energies may not be intuitive and should be analyzed carefully. By combining an Auger electron spectrometer (AES) with a low incident electron energy SEM (LE-SEM), we investigated the SEM contrast carefully by separating the secondary electron (SE) and back-scattered electron (BSE) components with high accuracy. For this, we modified an AES to measure the electron energy in the range of 0–0.6 keV with a sample bias voltage of 0 to −0.3 keV. We could clearly observe reversed brightness of gold and carbon (graphite) in BSE images when the energy of the incident electrons was reduced to 0.2–0.3 keV. In addition, reflected electron energy spectroscopy (REELS) is known to be a tool for chemical state analysis of the sample. We demonstrated that it is possible to study the electron states of graphite, diamond, and graphene by acquiring low incident energy REELS spectra from their surfaces with the newly modified AES. This will be a new method for analyzing the electron states of local areas of a surface.